Angular analysis of the decay B+ -> K+mu(+)mu(-) in proton-proton collisions at root s=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
The angular distribution of the flavor-changing neutral current decay B+ -> K+mu(+)mu(-) is studied in proton-proton collisions at a center-of-mass energy of 8 TeV. The analysis is based on data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb(-1). The forward-backward asymmetry A(FB) of the dimuon system and the contribution F-H from the pseudoscalar, scalar, and tensor amplitudes to the decay width are measured as a function of the dimuon mass squared. The measurements are consistent with the standard model expectations.
Keywords: PARTICLE; B-0